Characterization of Secondary Structure of Pig Hair Fiber Using Fourier-transform Infrared Spectroscopy. Issue 11 (2nd November 2022) - Mohan, N. H.; Choudhury, M.; Ammayappan, L.; Pathak, Prajwalita; Chakraborty, Sujay; Thomas, R.; Debnath, S.; Paul, Maitry; Sarma, D. K.
ABSTRACT: Hair or bristle is one of the key by-products of humane slaughter of pigs. In the present study, Fourier-transform infrared (FTIR) spectroscopy was used for examining protein secondary structure of hair fiber from different breeds of pigs (Ghungroo, Ninag Megha, Hampshire, and Duroc). Prominent amide I (1635–1648 cm −1 ) and amide II (1517–1528 cm −1 ) bands could be observed in the spectra. Differences in presence/absence of certain FTIR bands between breeds suggests influence of genetic background in the structure of hair fiber. Deconvolution resolved secondary structure of protein in amide I region of spectra into corresponding α-helix (38.0 ± 2.9%), β-sheets (32.2 ± 2.0%), β-turns (19.4 ± 3.1%) and unorganized structural components (10.3 ± 2.5%). Heating of fibers from 80°C to 120°C resulted in changes in amide regions and α-helix to β-sheet ratio of amide I band. Further, correlations were calculated between area under the curve of various FTIR bands and tensile properties of the fiber. Area of FTIR band at 1635 cm −1 was positively correlated with tenacity, initial modulus, extensibility, and work of rupture (r = 0.30 to 0.39). In nutshell, the study reveals subtle differences in secondary structure of hair with respect to breed or temperature treatment and suggests relation between FTIR spectral characteristics and tensile properties.